PENINGKATAN KUALITAS PEMBELAJARAN MELALUI PELATIHAN PENELITIAN TINDAKAN KELAS DI SD NUSA CENDANA INTERNATIONAL PLUS SCHOOL KUPANG - Konradus Silvester Jenahut; Osniman Paulina Maure; Timoteus Ajito; Chamelya V. C. Sene; Beatrix Purnama Sari; Mansuetus Mola; Rince S. M. Benu; Rozita Y. Lodo (LPPM Universitas Bina Bangsa, 2022)
A teacher needs to improve educational competence in order to improve the quality of education in Indonesia. One way to do this is through Classroom Action Research (PTK). Based on the results of observations and interviews at SD Nusa Cendana International Plus School (NCIPS) Kupang, it is known that there are many teachers who do not understand the practice of implementing PTK, its benefits in implementing the teaching and learning process, and how to implement PTK practically. Therefore, the San Pedro University Community Service Team (PKM) is interested in providing PTK training to NCIPS Kupang Elementary School teachers. The PKM was carried out on May 13-14, 2022 through 3 stages, namely the preparation, implementation, and evaluation stages. The results showed that the PTK training at SD NCIPS Kupang was able to have a positive impact on teachers, especially in understanding the implementation of PTK. In addition, the participants who participated in the activities were very enthusiastic and cooperative